Present Situation of the Nitrogen and Phosphorus Run-off Loss from Croplands in IntakeAreas of the Water Transfer Project from the Yangtze River to Huaihe River(the Sectionof the North of Huaihe River in Anhui) and Evaluation After Water Transfer Project - JIANG Xiaoying; ZHANG Haojie; WANG Lei (Renmin Zhujiang)
Based on the investigation of the planting structure, type and dosage of fertilizer inthe intake area (Anhui section) of water transfer project from the Yangtze River to Huaihe River,this paper estimates the nitrogen (N) and phosphorus (P) run-off loss from croplands and thecoefficients of pollution flowing into the river of the different intake areas, investigates thecontribution of non-point N and P loss from croplands into rivers to water quality, and predicatesthe change of influence of N and P run-off loss on the water quality after implementation of watertransfer project. The results show that: the excessive application of N and P fertilizer in thestudy area leads to a high amount of N and P loss,which has a great influence on the water qualityof Yinghe River, Xifei River, Cihuaixin River and Guohe River. With the implementation of the watertransfer project from Yangtze River to Huaihe River, the concentration of total nitrogen and totalphosphorus into the river continues to decrease and tends to be stable,and the concentration ofpollutants reduces, so the water quality will improve.